In Vitro and In Vivo Antitumor Activity of Lophocereus marginatus (DC.) S. Arias & Terrazas Endophytic Aspergillus versicolor and Metarhizium anisopliae Extracts Against the Murine Lymphoma L5178Y-R - Diana Laura Clark-Pérez; César Iván Romo-Sáenz; Jesica María Ramírez-Villalobos; Patricia Tamez-Guerra; Diana Caballero-Hernández; Ana Laura Delgado-Miranda; Andrés García; Joel Horacio Elizondo-Luevano; Cristina Rodríguez-Padilla; Ricardo Gomez-Flores (Microorganisms)
Cancer belongs to a group of diseases characterized by uncontrolled cell growth. The search for new effective treatments for cancer has led to the discovery of different molecules from plants, bacteria, and fungi with pharmacological use. Plant endophytic fungi are large producers of metabolites with antitumor properties. We aimed to evaluate the in vitro and in vivo antitumor potential of extracts from Lophocereus marginatus endophytic fungi. We obtained ethyl acetate and hexane extracts from the L. marginatus endophytes Metarhizium anisopliae and Aspergillus versicolor and evaluated their antitumor activity against murine L5178Y-R lymphoma cells and human peripheral blood mononuclear cells, using the 3-(4,5-dimethylthiazol-2-yl)-2-diphenyltetrazolium bromide reduction colorimetric technique. M. anisopliae and A. versicolor ethyl acetate extracts showed IC50 values of 9.168 ± 1.21 μg/mL and 13.51 ± 1.62, respectively, and selectivity indices > 30. We also observed that the maximum tolerated dose (100 mg/kg) of ethyl acetate extracts and the vehicle in BALB/c mice did not cause hepatotoxicity. In addition, we evaluated the effects of ethyl acetate extracts on survival and tumor volume in the L5178Y-R lymphoma tumor model. An increase in survival (17 d) was observed in mice treated with A. versicolor extract. Furthermore, it did not increase tumor volume during 10 d, as compared with the control groups without treatment, vehicle, and M. anisopliae extract, which had a maximum survival of 10 d. A. versicolor ethyl acetate extract showed in vitro and in vivo antitumor activity against lymphoma L5178Y-R, increasing mice survival.